AI PLATFORMS AND DIGITAL PEDAGOGY IN TEACHING FOREIGN LANGUAGES - Shaxnoza Alikulova; Abdurakhimova Shakhlo Nazirjon qizi; Juraboeva Farangiz Islombek qizi (TADQIQOTLAR, 2026)
Abstract The integration of artificial intelligence (AI) into foreign language education has fundamentally transformed both pedagogical approaches and learning experiences. By enabling adaptive learning, real-time feedback, and personalized instruction, AI platforms offer new opportunities for enhancing linguistic competence. However, despite these advantages, concerns remain regarding the reduction of human interaction, overdependence on technology, and ethical implications. This paper critically examines the role of AI within the framework of digital pedagogy, arguing that its effectiveness depends on a balanced integration with traditional teaching practices. Ultimately, AI should be viewed not as a replacement for educators, but as a complementary tool that supports more dynamic and learner-centered environments.